The Effect of Giving Cow Manure and Liquid Organic Fertilizer on Growth and Production Sweet Corn Plant : Zea mays Saccharata Sturt. - Pantas Simanjuntak; Lince Romauli Panataria; Ipan Evendra Purba (Tumbuhan : Publikasi Ilmu Sosiologi Pertanian Dan Ilmu Kehutanan, 2025)
The research aims to determine red onion plants' growth and production response (Allium cepa L.) on Planting Distance Treatment and Eco enzyme Concentration. This study used a Randomized Block Design (RBD) with two treatment factors. The first factor is the Planting Distance treatment consisting of 3 levels, namely J1 = 15 cm x 15 cm, J2 = 20 cm x 15 cm, and J3 = 25 cm x 15 cm. The second factor is the Eco enzyme Concentration, consisting of 3 levels, namely E1 = 0.8 ml ee / 240 ml water, E2 = 1.6 ml ee / 240 ml water, and E3 = 2.4 ml ee / 240 ml water. The study results showed that the Planting Distance treatment significantly affected root length and tuber diameter per sample. However, they had no significant effect on fresh tuber weight on the growth and production of shallots. The Eco enzyme concentration treatment had no significant effect on all observation treatments. The interaction between Planting Distance and the Eco enzyme concentration had no significant effect on all observation treatments.